Genomic data reveal a loss of diversity in two species of tuco-tucos (genus Ctenomys) following a volcanic eruption. Issue 1 (December 2017) - Hsu, Jeremy; Crawford, Jeremy; Tammone, Mauro; Ramakrishnan, Uma; Lacey, Eileen; Hadly, Elizabeth
Abstract Marked reductions in population size can trigger corresponding declines in genetic variation. Understanding the precise genetic consequences of such reductions, however, is often challenging due to the absence of robust pre- and post-reduction datasets. Here, we use heterochronous genomic data from samples obtained before and immediately after the 2011 eruption of the Puyehue-Cordón Caulle volcanic complex in Patagonia to explore the genetic impacts of this event on two parapatric species of rodents, the colonial tuco-tuco (Ctenomys sociabilis ) and the Patagonian tuco-tuco (C. haigi ). Previous analyses using microsatellites revealed no post-eruption changes in genetic variation inC. haigi, but an unexpected increase in variation inC. sociabilis . To explore this outcome further, we used targeted gene capture to sequence over 2, 000 putatively neutral regions for both species. Our data revealed that, contrary to the microsatellite analyses, the eruption was associated with a small but significant decrease in genetic variation in both species. We suggest that genome-level analyses provide greater power than traditional molecular markers to detect the genetic consequences of population size changes, particularly changes that are recent, short-term, or modest in size. Consequently, genomic analyses promise to generate important new insights into the effects of specific environmental events on demography and genetic variation.